Synthesis of Silver Nanoparticles By Chemical Reduction Method: Effect of Reducing Agent and Surfactant Concentration - Suriati, Ghazali; Mariatti, Jaafar; Azizan, Aziz (Universiti Malaysia Pahang, 2014)
Uniform, well-dispersed, silver nanoparticles (AgNPs) were prepared by a simple chemical reduction method. The particles were synthesized via the reduction of AgNO3 by trisodium citrate and ascorbic acid as a surfactant. The resulting AgNPs were characterized by X-ray diffraction analysis, transmission electron microscopy, and scanning electron microscopy. It was found that the size of the AgNPs ranged from 35–80 nm, with an average of 50 nm. In this study, the effects of trisodium citrate and ascorbic acid, which act as reducing agent and surfactant respectively on the morphology of the silver nanoparticles, were investigated. It was found that the increasing concentration of trisodium citrate resulted in decreasing size of silver nanoparticles, while increasing the concentration of ascorbic acid shows the opposite effect. Moreover, the quasi-spherical shape of as-synthesized silver nanoparticles is also more uniform with the increase of trisodium citrate. Meanwhile, a slight change in particle shape from quasi-spherical to polygonal was observed as the concentrations of ascorbic acid were increased.